An extraskeletal para-articular osteochondroma of Hoffa’s fat pad - Mulcahy, Hyojeong (Radiol Case Rep, 2015)
Extraskeletal para-articular osteochondromas are rather unusual tumors that arise in the soft tissues adjacent to the joint with no bony or joint continuity. We report a 25-year-old female who presented with a two-year history of right knee mass. Diagnostic imaging revealed a calcifying mass in the Hoffa’s fat pad of the knee. Roentgenographic, magnetic resonance imaging, and histopathologic features are presented.